Progress in diagnostics and therapy of obstructive lung diseases - Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2011)
Currently available clinical data indicate that obstructive lung diseases are still diagnostic and pharmacological problems. Overlap syndrome of asthma and COPD is illustrated in epidemiological reports which are related on final diagnosis of disease. However, no phenotype of overlap syndrome was described. The role of small airways inflammation in pathogenesis of obstructive diseases was documented and indicated the use of ultra-fine particles in pharmacological control. Clinical results confirmed useful of combined therapy in bronchodilation and inflammation control. For this reason the new generations of pharmacological combinations are on the way to clinical application. Ultra-LABA (ultra-long acting β2-agonists) like carmoterol and indacaterol are included into the new therapy. Similarly, ultra-LAMA (long-acting muscarinic antagonists) like aclidinium, glycopyrrolat or LAS-35201, GSK656398, GSK233705, OrM3 i CHF 5407 are under pre- and clinical examinations. Moreover, the new MABA (muscarinic antagonist to β 2-agonist) are in second phase of clinical evaluation.